Modelling the relationship between extreme temperature metrics and cardiovascular disease burden in India: Insights from a multi-state study on climate change challenges for 2011–2019 - Soundarya Soundararajan; Bhavani Shankara Bagepally; Jhalak Dhingra; Meghna P. Dinesh; K. Nimithamohan; Rakesh Balachandar (Clinical Epidemiology and Global Health)
Background: Climate change, particularly the rise in global temperatures, has significantly increased the burden of cardiovascular disease (CVD). Objective: The objective of this study is to investigate the CVD-burden attributable to temperature variations within the context of India's diverse climate conditions from 2011 to 2019. Methods: 2-m temperature data from the ERA5 dataset is used for estimating temperature metrics—average, median, mode, minimum, maximum, and variations. From the state-level temperature metrics, 2.5th and 97.5th percentiles are identified as extremes. CVD-burden data per 100,000 population, are sourced from the Global Burden of Disease study. The relationship between the temperature predictors and CVD burden is estimated using Poisson panel regression, followed by estimation of incidence rate ratios by exponentiation of coefficients. Results: A unit increase in average temperature increased the CVD-burden by ∼2.5 %. The 97.5th percentile consistently showed strong association with CVD-burden indices. The population attributable fraction for CVD mortality due to elevated average temperatures in India during the study period was estimated as 3.3 %. Significance: These findings reinforce existing research and underscore the impact of temperature variations on the CVD-burden, highlighting the need for public health interventions to mitigate the effects of temperature on cardiovascular health.